Exploiting PI3K/mTOR signaling to accelerate epithelial wound healing. (4th February 2013) - Castilho, RM; Squarize, CH; Gutkind, JS
<x xml:space="preserve">Abstract</x> The molecular circuitries controlling the process of skin wound healing have gained new significant insights in recent years. This knowledge is built on landmark studies on skin embryogenesis, maturation, and differentiation. Furthermore, the identification, characterization, and elucidation of the biological roles of adult skin epithelial stem cells and their influence in tissue homeostasis have provided the foundation for the overall understanding of the process of skin wound healing and tissue repair. Among numerous signaling pathways associated with epithelial functions, the PI3K/Akt/mTOR signaling route has gained substantial attention with the generation of animal models capable of dissecting individual components of the pathway, thereby providing a novel insight into the molecular framework underlying skin homeostasis and tissue regeneration. In this review, we focus on recent findings regarding the mechanisms involved in wound healing associated with the upregulation of the activity of the PI3K/Akt/mTOR circuitry. This review highlights critical findings on the molecular mechanisms controlling the activation of mTOR, a downstream component of the PI3K–PTEN pathway, which is directly involved in epithelial migration and proliferation. We discuss how this emerging information can be exploited for the development of novel pharmacological intervention strategies to accelerate the healing of critical size wounds.